Relationship between Circulating Protein p53 and High Sensitivity C-Reactive Protein in Central Obesity Men with Inflammaging - Rina Triana; Anna Meiliana; Eli Halimah; Andi Wijaya (The Indonesian Biomedical Journal, 2019)
BACKGROUND: The mechanism of aging goes along with age, one of which is characterized by cellular senescent, which occurs mostly in adipose tissue. Adipose tissue is the site of accumulation of large cell senescent, in the regulation of obesity and aging. Proteins p53 is marker for cell senescent, which are also known to induce inflammation. This study was aimed to determine the relationship between circulating protein p53 and high sensitivity C-reactive protein (hsCRP) in central obese men with inflammaging.METHODS: The study design is an observational study with cross-sectional approach. The subjects were 75 central obese men (waist circumference/WC > 90 cm), aged ≥ 45 years old. Subjects were divided into 2 age groups, those are middle age group: 45-59 years old (50.7%) and elderly group: ≥ 60 years old (49.3%). Examination of circulating p53 was done using enzyme-linked immunosorbent assay (ELISA) method, and the hsCRP examination was done by chemiluminescent method.RESULTS: It was found that there was a correlation between circulating p53 and hsCRP in elderly (r=-0.414; p<0.05) but not in middle age (r=-0.127; p=0.449).CONCLUSION: From this study, it is assumed that more senescence cells in elderly are resulting in increased chronic inflammation.KEYWORDS: aging, senescent, inflammaging, protein p53, hsCRP